2016
DOI: 10.1111/jcpt.12462
|View full text |Cite
|
Sign up to set email alerts
|

Can we document the practice of dispensing? A systematic review

Abstract: SUMMARYWhat is known: Documentation is a process indicator utilized to evaluate quality clinical pharmacist services. In this framework, documentation of dispensing, besides supporting patient care, allows evaluation of the impact of counselling. Objective: To identify and assess studies of documentation by pharmacists in the dispensing process. Method: A systematic review was carried out according to the following steps: (i) identification of studies in the following databases: PubMed/Medline, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
(319 reference statements)
0
5
0
Order By: Relevance
“…Another barrier mentioned was the lack of an electronic health record (EHR). Several studies report the beneficial impact of EHRs on patient safety and efficiency, such as improvement in quality of care, prescribing safety, disease management, clinical documentation, work practice, preventive care, and in the volume of communication between pharmacists and the healthcare team [ 62 64 ]. There is the Brazilian National Electronic Health Record (e-SUS AB), a system that gathers all of the patient's health information and shares it with all members of the healthcare team.…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier mentioned was the lack of an electronic health record (EHR). Several studies report the beneficial impact of EHRs on patient safety and efficiency, such as improvement in quality of care, prescribing safety, disease management, clinical documentation, work practice, preventive care, and in the volume of communication between pharmacists and the healthcare team [ 62 64 ]. There is the Brazilian National Electronic Health Record (e-SUS AB), a system that gathers all of the patient's health information and shares it with all members of the healthcare team.…”
Section: Discussionmentioning
confidence: 99%
“…When using QIs, it is often impossible to distinguish between a deficient clinical practice and a lack of appropriate documentation in pharmacy records. The literature has reported challenged and limited clinical documentation of patient care in community pharmacy . Our results may also suggest that quality of clinical practices is deficient.…”
Section: Discussionmentioning
confidence: 90%
“…The results of this systematic review demonstrate the positive influence of drug dispensing on the health outcomes of patients attending community pharmacies. Studies that address drug dispensing usually assess the quality of the practice showing a non-systematized and undocumented process [ 26 , 30 , 58 ]. Several strategies have been proposed to qualify this service, such as the development of instruments to support the practice and training pharmacists and pharmacy teams [ 27 , 38 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have reported the impact of different clinical pharmacy services on the health outcomes of patients, such as medication review [ 21 ], medication reconciliation [ 22 ], medication synchronization [ 23 ], and medication therapy management [ 24 , 25 ]. However, there is a lack of evidence for the impact of drug dispensing on health outcomes, and studies have mainly addressed certain aspects of this practice, such as the evaluation of the structure, process, and quality of the service [ 26 30 ]. Thus, high-quality studies are needed to evaluate the impact of drug dispensing on clinical, humanistic, and economic outcomes of patients.…”
Section: Introductionmentioning
confidence: 99%